2019
DOI: 10.1038/s41598-018-37087-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties and productivity in two long-term crop rotations differing with respect to organic matter management on an Albic Luvisol

Abstract: This study was based on a three-factor experiment carried out since 1980 on a loamy sand (Albic Luvisol) in which arable crops were grown in two 4-years rotations: RotA (grain maize, winter wheat, spring barley and silage maize) and RotB [grain maize, winter wheat plus mustard green manure (GM), spring barley and grass–clover ley (GCL)]. The soil in RotB with an increased input of OM (GM and 1-year GCL) accumulated significantly larger amounts of soil organic carbon and soil microbial biomass C, had higher act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
12
0
5
Order By: Relevance
“…Studies show that continuous cropping has a negative contribution to soil chemical traits and nutrient quality compared to rotational cropping system. The present results showed that FC significantly increased the content of TN, AN, TK, AK in soil, compared with CC system (Table 1), which suggests that FC system may improve soil physicochemical characteristics, and enhance nutrient content [31][32][33][34][35][36][37][38]. Mean±standard error, FC-First year vegetable, second subsequent year P.odoratum; CC-First year P. odoratum, second subsequent year P.odoratum; CK-No crop planted in the first and second subsequent year; N-Nitrogen; P-Phosphorus; K-Potassium.…”
Section: 9soil Nutrients Improved Under Fc Systemmentioning
confidence: 89%
“…Studies show that continuous cropping has a negative contribution to soil chemical traits and nutrient quality compared to rotational cropping system. The present results showed that FC significantly increased the content of TN, AN, TK, AK in soil, compared with CC system (Table 1), which suggests that FC system may improve soil physicochemical characteristics, and enhance nutrient content [31][32][33][34][35][36][37][38]. Mean±standard error, FC-First year vegetable, second subsequent year P.odoratum; CC-First year P. odoratum, second subsequent year P.odoratum; CK-No crop planted in the first and second subsequent year; N-Nitrogen; P-Phosphorus; K-Potassium.…”
Section: 9soil Nutrients Improved Under Fc Systemmentioning
confidence: 89%
“…Grain yield was higher following the mixing of the Aw and B layers in the two-year study period than in the CS treatment. Crop straw, which could increase organic matter content [ 38 ] and aggregate stability [ 39 , 40 ], should be incorporated into the subsoil during Aw and B layer mixing. The results of the present study indicate that the positive effects of mixing the Aw and B layer soils on improved crop yield in Albic soil using different subsoil mixing ploughs [ 21 , 24 , 25 ] (i.e., in the TSMP, FMSP, and TSIMP treatments) could be sustained for at least two years.…”
Section: Discussionmentioning
confidence: 99%
“…These findings can be explained by the fact that crop yield increases due to the fact that green manure as adds N and has additional beneficial effects on soil properties (Skoufogianni et al, 2013). It is well established that the incorporation of quality organic inputs provides rapid and efficient accumulation of nutrient uptakes for the crop by releasing nutrients in synchrony with plant demands (Martyniuk et al, 2019). The results of Dhima et al (2009) indicated also that green manure of aromatic species can increase the final grain yield by reducing weed infestation in maize crops.…”
Section: -2018 2018-2019mentioning
confidence: 99%
“…Green manure crops of N-fixing legumes supply N to the cropping system and should therefore be considered as an important component of each crop rotation system (Martyniuk et al, 2019). The beneficial effects of Trifolium pratense L. as green manure on the number of grains per corncob and the final maize grain yield have been observed by Tejada et al (2008).…”
Section: Introductionmentioning
confidence: 99%